Character Design in Golek Puppet: Daster Rombeng Warrior and the Powerful Storyteller - Chotimah, Fanny; Handriyotopo, Handriyotopo (Universitas Negeri Medan, 2024)
Creative documentaries are not yet popular in Indonesia. So it needs to be produced to enrich the treasury of documentary films in the archipelago. The public needs to be given knowledge to recognize the variety of narratives and storytelling in the documentary category. This film can contribute as an alternative viewing for the public and also as an educational media related to the virtues of the storytelling tradition. The creation of this film aims to be a medium to revive the culture of storytelling in society based on the values ​​of the storytelling tradition itself. The character of the film as a puppet puppet puppet story figure that can be used as an illustration of the scene in visualizing the fairy tale of Si Leungli and Geber-geber Hihid Aing. The method of creating film art through research stages for enkranation or transfer of vehicles from the short story Pendekar Daster Rombeng and Pendongeng Sakti in the research and production stages of puppets as a creative strategy and artistic arrangement of the film.